China denies cyber-spying, but seen using stolen exile Tibetan data. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2009)
The article reports on the investigation made by teams of cyber experts in Toronto and Cambridge to China. It found that computers in China had hacked into and stolen data from 1,239 computers from 103 countries. Moreover, the findings are based on the request for investigation from the Dalai Lama's office.